The Phenomenon of Self-Diagnosis of Mental Health in The Era of Mental Health Literacy - Diandra Thufailah Sukmawati; Syamsu Yusuf; Nadia Aulia Nadhirah (Journal of Education and Counseling (JECO), 2023)
Awareness related to mental health literacy can lead to issues in the form of self-diagnosis, which is when a person diagnoses himself based on literature circulating on the internet, then identifies himself as having a mental condition without confirmation from a professional. Therefore, the purpose of this study is to be able to further examine the phenomenon of self-diagnosis of mental health in the era of mental health literacy using the sytematic literature study method. The systematic literature method is used to collect, identify, and analyze literature that has been found systematically. The results obtained are a correlation between self-diagnosed and mental health literacy, as well as the potential positive impact of self-diagnosed.